Regulasi Diri Umat Hindu di Kabupaten Kudus - Musta'in, Musta'in; M. Suharsono; Mochamad Widjanarko (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to determine the self-regulation of Hindus in kudus district, In phenomenological research, the data collection methods used focus on in-depth interviews and narratives, In this study, the criteria chosen to be informants are Hindus who live and settle in kudus district, Central Java, namely those who have been Hindu since childhood and actively live their worship. The results of this study are related to strengthening self-regulation in various forms. There are various forms of strengthening self-regulation both from the family environment, the surrounding environment or friends as well as the forms of encouragement that are given vary in the form of verbal or verbal support. Based on the results obtained in the interviews that have been conducted, informant I, informant II, informant III revealed that they received reinforcement from their closest people even though for informant II, the environment also plays a role in self-regulation and self-evaluation is important for improvement. Informants get enough support from various parties in worship, although worship facilities for Hindus in Kudus are still inadequate and there are a small number who do not like it. This does not make them hesitate in worshiping.